Transient Expression of GATA3 in Hematopoietic Stem Cells Facilitates Helper Innate Lymphoid Cell Differentiation - Tufa, Dejene M.; Yingst, Ashley M.; Shank, Tyler; Shim, Seonhui; Trahan, George Devon; Lake, Jessica; Woods, Renee; Jones, Kenneth L.; Verneris, Michael R. (Frontiers in Immunology, 2019)
Abstract Helper Innate lymphoid cells (ILCs) are tissue resident lymphocytes that play a critical role in a number of biological processes. Several transcription factors are required for the differentiation of hematopoietic stem cells (HSCs) into ILCs. Recent studies demonstrate GATA3 as a transcriptional regulator that plays an essential role in ILC development. We aimed to modulate the differentiation of human cord blood-derived CD34+ cells into ILCs by transient and ectopic expression of mRNA encoding transcription factors known to be important for ILC lineage differentiation, including GATA3, TOX, NFIL3, ID2 and RORt. Using this experimental protocol, only GATA3 significantly modulated HSCs to differentiate into helper ILCs. Transient overexpression of GATA3 drove the emergence of CD34+α4β7+ early ILC progenitors during the first few days of culture. These ILC progenitors further acquired IL-7Rα and CD117 to give rise to immediate ILC precursors. In support of these findings, analysis of the genes induced by GATA3 in HSCs showed an upregulation of those associated with ILC development. Moreover, we show GATA3 also acts on more committed progenitors and significantly shifts the differentiation of progenitors away from the ILC1/NK lineage to the ILC2 and ILC3 lineage. In summary, transient overexpression of GATA3 mRNA in CD34+ HSCs enhances the differentiation of HSCs into the helper ILC lineages, at the expense of NK cell development.